The Impact of Student Response Time in a Gamified Learning Environment on Programming Skill Development (The International Journal of Educational Sciences and Arts, 2025)
The study aimed to investigate the effect of different response times for educational activities (time-limited vs. unlimited time) in a gamified e-learning environment on the development of programming skills among middle school students. The study used a quasi-experimental design. The sample consisted of 60 third-year middle school students from Al-Imam Al-Nawawi School, who were randomly assigned to two groups based on the response time model (time-limited vs. unlimited time). The results of the study showed a statistically significant difference at the 0.05 level in favor of the group that used the unlimited time response model, with an average score of 26.23 compared to the time-limited response group, which had an average score of 22.80. The calculated t-value (4.731) was greater than the critical t-value (1.98), indicating the superiority of the unlimited time response model in developing programming skills. The study recommended using time-unlimited activities in gamified e-learning environments, especially for teaching programming skills, to reduce anxiety caused by time pressure, and integrating interactive strategies based on digital games into the curriculum.
Keywords: Gamification; Response Time; Programming Skills